(untitled) (International journal of artificial intelligence, 2026)
Speaking anxiety is a common challenge faced by many English as a Foreign Language (EFL) learners around the world, often hindering their oral communication and overall language development. This study investigates effective teacher strategies to minimize speaking anxiety in classroom settings. While using a mixed-methods approach, data were collected through observations in the classroom, questionnaires involving 30 beginner level EFL learners. The study identifies key strategies such as pair work, role play, positive feedback, and supportive teacher-student interaction that contribute significantly to minimizing anxiety levels. Findings suggest that implementing these strategies improves students’ confidence, participation, and speaking performances. This research provides practical implications for teachers seeking to create a more supportive and anxiety-free learning environment in EFL classrooms.